PENGGUNAAN FEM (FINITE ELEMENT METHOD) DALAM MEMETAKAN MEDAN LISTRIK PADA PERMUKAAN ISOLATOR JENIS PIN DAN POST 20 KV SERTA UDARA DI SEKITARNYA - Warsito, Agung; Facta, M.; Azmi, Safarul (Transmisi, 2008)
Abstract. Electric field is the area which still be influenced electricity from certain electric charge. Based on WHO recommendation in 1990, electric field limits which is allowed at public during 24 hours per day is 5 kV/m. Saluran Udara Tegangan Menengah (SUTM) has big electric field intensity. Therefore, required a study to map the electric field and know the distance that a man is enabled to stay at that electric field limits. The analysis to map the electric field at this final report is by using the Finite Element Method GEM). FEM is a numerical method for solving problems of engineering and mathematical physics. The analysis is assist by using MATLAB 7.0.1 and ANSYS 9.0 as benchmarking prograrn. From the result of simulation, the transformation of electric mast construction at pin type insulator had an effect on the electric field intensity value only at the direction from middle position of conductor upward. The electric mast construction using post type insulator has bigger electric field intensity than the electric mast construction using pin type insulator if evaluated from the same distance. Keywords : electric field, finite element method, and distribution line